La fiesta del Inti Raymi en la construcción del Estado plurinacional en el Ecuador - Luis Alberto Tuaza (Les Cahiers ALHIM)
This article analyzes the festival of Inti Raymi, promoted in recent years by various government intitutions in Ecuador. With an ethnographic approach to indigenous communities and a review of academic discourse surrounding plurinationality, it establishes a crisicism of the attempt to build the plurinational State through the celebration of this Andean festival. In conclusion it is considered that Inti Raymi, far from promoting the celebration of the multicultural nation, merely continues the process of folklorization of indigenous people while the current problems facing indigenous people remain invisible.